Impact of mobile applications on adherence to cancer treatment: a systematic review and meta-analysis protocol - Ana Katherine Gonçalves; Michelly Nóbrega Monteiro; Kleyton Santos Medeiros; Ricardo Ney Cobucci; Janice França Queiroz; Weruska Alcoforado Costa; Beatriz Stransky (BMJ Open, 2019)
Introduction The number of patients taking oral chemotherapy is increasing around the world. It is essential to maximise the adherence to oral chemotherapy to improve the overall survival and life expectancy of the patients. In this systematic review and meta-analysis, we aim to evaluate the effectiveness of mobile applications in improving the adherence to oral chemotherapy and adjuvant hormonal therapy in cancer survivors.Methods and analysis MEDLINE, Embase, LILACS, clinicaltrials.gov, Scopus and the Cochrane Central Register of Controlled Trials will be searched for randomised or quasi-experimental studies published between January 2009 and July 2019. This systematic review and meta-analysis will include studies investigating the use of mobile applications by cancer survivors to aid adherence to oral chemotherapy and adjuvant hormonal therapy. Patient education, reminder tools, calendars, pillboxes and electronic reminders will not be evaluated. The primary outcome will be the improvement in adherence to anticancer drugs. The secondary outcomes will be an improvement in the overall survival and life expectancy, improved quality of life and control of cancer-related symptoms. Three independent reviewers will select the studies and extract data from the original publications. The risk-of-bias will be assessed using the Cochrane risk-of-bias tool. Data synthesis will be performed using the Review Manager software (RevMan V.5.2.3). To assess heterogeneity, we will compute the I2 statistics. Additionally, a quantitative synthesis will be performed if the included studies are sufficiently homogenous.Ethics and dissemination This study will be a review of the published data, and thus, ethical approval is not required. Findings of this systematic review will be published in a peer-reviewed journal.PROSPERO registration number CRD42018102172.